Cover, Editorial Board, Daftar Isi - I Wayan Batan (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2022)
Cover, Editorial Board, Indeks, dan Daftar Isi